Pengaruh Media Sosial terhadap Peningkatan Penjualan UMKM Fashion di Era Industri 4.0 di Kota Serang - Vera Maria; Febri Haerurrohman; Ibnu Khoir Ar Razak (STIKes Ibnu Sina Ajibarang, 2025)
Digital transformation in the industrial era 4.0 has brought fundamental changes to marketing strategies, especially for micro, small and medium enterprises (MSMEs). This study aims to analyze the effect of social media use on increasing sales and income of fashion MSMEs in Serang City. Quantitative methods are used with a simple linear regression approach, and data collection through questionnaires to 61 MSME players. The results of the analysis show that the use of social media has a positive and significant effect on increasing sales and income. The normality test shows that the residuals of model Y2 are normally distributed, while model Y1 is not. In addition, the Glejser test results show indications of heteroscedasticity in both models. Nonetheless, the models remain valid for use as they meet the minimum sample size requirement. These findings confirm that strategic utilization of social media can improve the business performance of fashion MSMEs, so it is recommended as part of an adaptive digital strategy in facing competitive challenges in the era of digital transformation.